2014
DOI: 10.1038/jcbfm.2014.152
|View full text |Cite
|
Sign up to set email alerts
|

MiR-181a Regulates Blood-Tumor Barrier Permeability by Targeting Krüppel-Like Factor 6

Abstract: Blood-tumor barrier (BTB) constitutes an efficient organization of tight junctions that impairs the delivery of therapeutic drugs. However, the methods and molecular mechanisms underlying the BTB opening remain elusive. MicroRNAs (miRNAs) have recently emerged as key regulators of various biologic processes and therapeutic targets. In this study, we have identified microRNA-181a (miR-181a) as a critical miRNA in opening BTB. MicroRNA-181a expression was upregulated in glioma endothelial cells (GECs), which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 37 publications
(40 reference statements)
2
40
0
Order By: Relevance
“…Several studies of micro-RNAs and other drugs on the permeability of the BTB showed similar results. For example, overexpression of miR-34c, miR-181a, and EMAPII increased the permeability of the BTB by changing the expressions and distributions of tight junctionrelated proteins ZO-1, claudin-5, and occludin (Ma et al, 2014b;Li et al, 2015;Zhao et al, 2015), and the common feature is that they increased the permeability of the BTB through paracellular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of micro-RNAs and other drugs on the permeability of the BTB showed similar results. For example, overexpression of miR-34c, miR-181a, and EMAPII increased the permeability of the BTB by changing the expressions and distributions of tight junctionrelated proteins ZO-1, claudin-5, and occludin (Ma et al, 2014b;Li et al, 2015;Zhao et al, 2015), and the common feature is that they increased the permeability of the BTB through paracellular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro BTB model was established by coculturing hCMEC/D3 with U87-MG in a Transwell permeable support system (0.4 mm pore size; Corning, Corning, NY, USA) as previously described (25). Briefly, hCMEC/D3s cells were seeded at 2 3 10 5 per well in 6-well plates on the upper side of the inserts with EBM-2.…”
Section: Establishment Of Btb Model In Vitromentioning
confidence: 99%
“…While EC-EV released miRNA are understood to play a distinct role in endothelial function, how miRNAs derived from EC-EVs contribute to the characteristic loss of coordination leading to development of sepsis remains unclear (►Table 2). [75][76][77][78][103][104][105][106][107]…”
Section: Extrinsic Endothelial Mirna Dysregulation In Vascular Diseasementioning
confidence: 99%